Prevalence of Smoking Among Spontaneous Pneumothorax Patients and Its Impact on Treatment in Syria Country: A Cross‐Sectional Study - Muhanad Munzer; Nafiza Martini; Mhd Mustafa Albitar; Lilas Channiss; Mohammed Martini; Hussam Al bardan (Health Science Reports)
ABSTRACT Background and Aims Spontaneous Pneumothorax (SP) is a case where air is collected in the pleural space, with smoking recognized as a major risk factor. Despite the global burden of SP, there is limited research on its prevalence and recurrence in Middle Eastern populations, particularly in Syria. This study aims to evaluate the prevalence of smoking among SP patients in Syria and investigate its impact on SP recurrence, providing insights that could guide more effective treatment strategies in regions with high smoking rates. Methods A cross‐sectional study was conducted on patients with spontaneous pneumothorax treated at two university hospitals in Syria from January 2016 to January 2021. Data on demographics, smoking habits, treatment types (conservative, intercostal drainage, and surgical), and recurrence were collected. Pearson's Chi‐square test was used to analyze the association between smoking and SP recurrence. Results This study included 156 patients divided into 135 males and 21 females. One hundred and twenty‐five patients were smokers (80.13%), and 118 were men. A recurrence rate of 43.6% (68 patients) was observed in the complete sample. We found a relationship between recurrence and smoking (p = 0.002) and between recurrence and male gender (p = 0.015). In comparison with the three types of treatment, intercostal drainage had the highest recurrence rate (52.9%), and surgical treatment had the lowest rate (6.8%). In both surgical and conservative treatments, all recurrent cases were male smokers. Conclusion In Syria, the high prevalence of smoking, especially among males, significantly increases the risk and recurrence of spontaneous pneumothorax. These findings highlight the need for targeted smoking cessation programs and should inform the selection of treatment strategies for SP patients, particularly those at high risk of recurrence.